Curved hole drilling by laser manipulation of a heat spot inside glass - Miyakoda, Kaito; Sunayama, Koki; Sakamoto, Kosuke; Tokunaga, Daijiro; Hidai, Hirofumi; Matsusaka, Souta (Precision engineering, 2023)
A fiber fuse is a heat spot that propagates toward a light source with bright emission. This occurs when the fiber transmits a high-intensity laser and is triggered by heating with contamination on the edge. Glass is transparent and allows near-infrared light to pass through it at room temperature; however, it absorbs light at high temperatures. Hence, once a heat spot forms in the glass, it maintains a high temperature and propagates toward the light source. In straight hole drilling, this phenomenon of leading the heat spot toward the glass surface and ejecting the heated glass to form a hole has been utilized. In this study, heat-spot manipulation was demonstrated by laser scanning, and curved modification was observed. The emissions did not follow the scan and disappeared at high scanning speeds. The conditions under which the emission followed the scan were experimentally determined by changing the scanning speed. Curved hole formation was also demonstrated by manipulation of the heat spot and ejection of the heated glass. The obtained hole had a curvature radius of approximately 320 μm, length of approximately 860 μm, and diameter of approximately 17 μm. •Heat spot manipulation was demonstrated using laser scanning.•A curved hole formation was demonstrated by the ejection of the heated glass.•The limitations of heat spot manipulation were elucidated experimentally.